Unlocking the Increase of Land and Building Tax Revenue in Bantul Regency - Rina Mawarti Muji Astuti (Universitas Teknologi Yogyakarta, 2023)
National development is an activity that continuously occurs and aims to improve human quality and social welfare; capital is needed to finance this process. One of the sources of capital in the implementation of development in Indonesia is the Rural-Urban Land and Building Tax, among the taxes collected from the community. This research discusses the obstacles to increasing land and building tax revenues. This research was conducted in the Bantul Regency. -Efforts to increase tax revenues include conducting PBB monitoring, innovating the Bantul LaPak application, holding the Bantul Tax Award event, and holding mobile car innovations. Among the programs mentioned above, the mobile car program is a program that plays a significant role in increasing land and building taxes in the Bantul Regency. With this mobile car, the services carried out can be closer to people who live far from the city where they live, called the ball pick-up system. In its development, the mobile car program can increase Land and Building Tax revenue from 2017 to 2019. Land and Building Tax revenue reached a predetermined target, where out of 933 hamlets in Bantul Regency, 777 hamlets have been served increase in revenue, namely in 2017 it increased by 78%, then in 2018 it became 82% or 36.5 billion in 2017, then experienced an increase in 2018 amounting to 39.3 billion, then in 2019 it reached 54.7 billion.